Perancangan Aplikasi Sistem Informasi Akuntansi Laporan Keuangan Menggunakan Microsoft Access 2016 - Siti Sopiah; Arif Afriady (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Cahaya Printing is a company engaged in printing services and is located in Bandung. Financial reports are important information for internal and external parties. The purpose of this study is to identify and identify the weaknesses of the companys accounting information system, as well as to design the application of financial statements according to the needs and to know the implications. The research method used is a qualitative method with a case study and development approach. Microsoft Access 2016 as a design tool as well as document flowcharts and DFD as tools for the flow of the system. Recording and reporting in the company already uses Microsoft Excel, the results of the design of financial report applications in the form of a list of journal transactions, a list of general ledger transactions, trial balances, income statements, reports of changes in equity, statements of financial position, cash flow statements, cash income and expenditure reports, and a list of charts of accounts. This application is also considered more effective and efficient in overcoming problems related to the previous system